Hepatoprotective Effect of Satureja Khuzestanica Essential Oil and Vitamin E in Experimental Hyperthyroid Rats: Evidence for Role of Antioxidant Effect - Raheleh Assaei (Iranian Journal of Medical Sciences, 2014)
Background: Hyperthyroidism is associated with liver oxidative stress causing liver dysfunction in many hyperthyroid patients. The hepatoprotective effect of Satureja Khuzestanica Essential Oil (SKEO), as herbal origin antioxidant and anti-inflammatory agent on the hyperthyroidism induced hepatotoxicity and oxidative stress is investigated. Methods: Adult male sprague dawley rats were divided into categories of; control (group C), hyperthyroid (group H), hyperthyroid with olive oil (group H+O), hyperthyroid with vitamin E (group H+E), hyperthyroid with SKEO (group H+S), combination of hyperthyroid with vitamin E and SKEO (group H+S+E). Hepatoprotective and antioxidant properties of SKEO with or without vitamin E in hyperthyroid rats were then investigated. Results: Serum Aspartate Transaminase (AST) and Alanine Transaminase (ALT) activities reduced significantly in H+O, H+E, H+S and H+S+E groups in comparison with hyperthyroid rats. Enzymes activities returned to normal in H+S+E group. Hepatic Malondialdehyde (MDA) was reduced in H+E, H+S and H+S+E groups in comparison with hyperthyroid rats. The most significant MDA reduction was in the H+S+E group. Glutathione Peroxidase (GPx) and Glutathione Reductase (GR) activities increased in H+E, H+S and H+S+E groups in comparison with group H. The largest increment in GPx and GR activities were in the H+S+E group. Glutathione level did not change in any group in comparison with the control group. Conclusion: Administration of SKEO has hepatoprotective effect in hyperthyroid rats and is more effective when used in combination with vitamin E.